The impact of walking in different urban environments on brain activity in older people. Issue 1 (2nd January 2020) - Neale, Chris; Aspinall, Peter; Roe, Jenny; Tilley, Sara; Mavros, Panagiotis; Cinderby, Steve; Coyne, Richard; Thin, Neil; Ward Thompson, Catharine
ABSTRACT: Neurourbanism looks to understand the relationship between urban environments and mental well-being and is well placed to assess the role of these environments on the urbanised and ageing global population. This study builds on research using mobile electroencephalography (EEG) to understand the impact of urban environments (busy, quiet and green urban spaces) on brain activity. Ninety-five older participants aged over 65 years undertook one of six walks in an urban neighbourhood, transitioning between two distinct environmental settings. This study explores changes in alpha (associated with relaxation) and beta (associated with attention) brain activity recorded during walking in differing urban environments. Neural activity significantly varies as participants walk between urban busy and green settings, with reduced levels of low beta activity in the green setting, suggesting attention changes consistent with Attention Restoration Theory. Levels of alpha activity significantly varied between the urban busy and the urban quiet settings, with increases in the urban busy setting. There were no significant differences in EEG activity between the urban green and urban quiet settings, suggesting that the magnitude of environmental contrast between the urban busy context and other urban settings is an important factor in understanding the effects of these spaces on brain activity.